STRATEGI REBRAND USAHA BERBASIS RUMAH TANGGA MELALUI DESAIN ULANG TEMPAT USAHA DI KECAMATAN PANDAAN, KABUPATEN PASURUAN - Rolalisasi, Andarita; Kusumaningayu, Intan; Iffiyah, Khoudiy; Hutama, Shinta Fiqi (LPPM ITATS, 2020)
This paper presents the community service (PKM) implementation for home based enterprises Pia ?Mahen?. The purpose is re-design working place as a producing place and as a training center of Pia making through provided a layout design. These two functions took a same place currently. This condition interfere each functions. This PKM is involving students for apply their design knowledge. The implementation method is used technical assistance for re-design of the working place and the training center. Through the redesign of working place Pia ?Mahen? is expected to be increasingly widely known as a producing place of Pia and a training center of Pia making.